PELATIHAN TOEFL BAGI MAHASISWA DI PESANTREN AL-MASHDUQIE DI KAMAL BANGKALAN - Eka Susylowati; Meria Zakiyah Alfisuma; Tri Pujiati; Dede Rosyadi ZA; Bima Kurniawan (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
TOEFL (Test of English as Foreign Language) training is a necessity for students in Islamic boarding schools, especially for final year students who will take the TOEFL test as one of the requirements for graduation or when entering the world of work. One of the pesantrens that is used as a partner is Pesantren Al-Mashduqie, Kamal, Bangkalan. The main problem faced by the partner is the lack of understanding related to TOEFL so that the TOEFL scores of students in the AlMashduqie Islamic Boarding School are still not in line with the expected target. Therefore, community service activities carried out by the academic community in the English Literature Study Program need to be carried out as a form of practicing the Tri Dharma of Higher Education. The purpose of this activity is to increase the TOEFL score of students in the Al-Mashduqie Islamic Boarding School in Bangkalan Regency. The dedication method used during the training activities are the lecture method, question and answer, and practice working on TOEFL questions in accordance with the material that has been prepared by the presenters. The results of the community service activities show that there is an increase in the TOEFL score of students in Al-Mashduqie Islamic Boarding School environment, Kamal, Bangkalan